1997
DOI: 10.1183/09031936.97.10122853
|View full text |Cite
|
Sign up to set email alerts
|

Fibre types in skeletal muscles of chronic obstructive pulmonary disease patients related to respiratory function and exercise tolerance

Abstract: F Fi ib br re e t ty yp pe es s iin n s sk ke el le et ta al l m mu us sc cl le es s o of f c ch hr ro on ni ic c o ob bs st tr ru uc ct ti iv ve e p pu ul lm mo on na ar ry y d di is se ea as se e p pa at ti ie en nt ts s r re el la at te ed d t to o r re es sp pi ir ra at to or ry y f fu un nc ct ti io on n a an nd d e ex xe er rc ci is se e t to ol le er ra an nc ce e A group of 22 COPD patients and 10 healthy control subjects were studied. In COPD patients, vital capacity (VC) and forced expiratory volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
4
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 27 publications
6
77
4
3
Order By: Relevance
“…There is evidence to suggest that a decrease in the proportion of fatigue-resistant slow fibres in skeletal muscle affects stamina. 42 In patients with chronic obstructive pulmonary disease the scarce oxygen availability and/or the inactivity and physical deconditioning are thought to cause fibre transformation, with an increase in the proportion of the fast fatiguable fibres that are responsible for lactate production and fatigue at low work rates. Investigations into the fibre composition in skeletal muscle biopsies from WS patients, as well as stamina tests, would be required to determine if this is also the case in Williams syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that a decrease in the proportion of fatigue-resistant slow fibres in skeletal muscle affects stamina. 42 In patients with chronic obstructive pulmonary disease the scarce oxygen availability and/or the inactivity and physical deconditioning are thought to cause fibre transformation, with an increase in the proportion of the fast fatiguable fibres that are responsible for lactate production and fatigue at low work rates. Investigations into the fibre composition in skeletal muscle biopsies from WS patients, as well as stamina tests, would be required to determine if this is also the case in Williams syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship between oxidative enzyme activities and lactic acidosis in COPD patients has also been shown. In addition, there was also evidence of muscle fiber type alterations in COPD patients who showed decrease in the proportion of fatigueresistant slow fibers 46) . As previously indicated, some patients with COPD have a higher than normal mixed venous partial pressure of oxygen during exercise.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, other investigators [4,6,7] have reported that COPD patients have a lower proportion of type I fibres and an elevation in the per cent of type II fibres in the vastus lateralis muscle. In addition, two investigations [8,9] have demonstrated altered MyHC expression in vastus lateralis muscle biopsies from COPD patients. These investigations collectively indicate that alterations in muscle fibre composition induced by COPD may differ between humans and animals.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Such a shift would predispose skeletal muscle to greater fatigability and impair exercise tolerance. In addition, COPD patients with reduced work capacity present with alterations in peripheral skeletal muscle composition and structure, including altered fibre composition [4,6,7] and myosin heavy chain (MyHC) expression [8,9], atrophy of peripheral skeletal muscle type I and/or II fibres [7,10,11], and reductions in lean body mass [12]. Therefore, altered metabolic pathways, fibre transformation and fibre atrophy appear to underlie problems of enhanced skeletal muscle fatigability, reduced force production and exercise intolerance in patients with COPD.…”
mentioning
confidence: 99%